2018
DOI: 10.1371/journal.pone.0207860
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship of resilience, anxiety and injuries in footballers: Structural equations analysis

Abstract: Resilience is a psychological characteristic which enhances personal assets and protects individuals from potential negative effects of various stressors. While this topic has been considered in the separate context of sports injuries and anxiety states, these issues have rarely been considered together. The objective of this study is to analyse the association between motivation to overcome injuries in football and the state of anxiety caused by those injuries. One hundred and eighty-five footballers from Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
(51 reference statements)
1
23
0
1
Order By: Relevance
“…Similarly, a study by Trigueros, Aguilar-Parra, Álvarez, Cangas & López-Liria [65] showed that those athletes who had high levels of resilience were negatively related to anxiety. In addition, those athletes who had high levels of resilience showed less anxiety about injuries and a shorter convalescence time [66]. On the other hand, a study conducted by García-Secades, Molinero, Ruiz-Barquín, Salguero, De la Vega & Márquez [67] on professional athletes showed that those with high levels of resilience negatively predicted stress, increasing their sense of well-being during competition.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Trigueros, Aguilar-Parra, Álvarez, Cangas & López-Liria [65] showed that those athletes who had high levels of resilience were negatively related to anxiety. In addition, those athletes who had high levels of resilience showed less anxiety about injuries and a shorter convalescence time [66]. On the other hand, a study conducted by García-Secades, Molinero, Ruiz-Barquín, Salguero, De la Vega & Márquez [67] on professional athletes showed that those with high levels of resilience negatively predicted stress, increasing their sense of well-being during competition.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a wider approach to injury in high-performance sport, McGregor [15] took into consideration a range of factors such as team environment, facilities, athletes-coach relationship, technical-tactical skills, and different psychological aspects such as confidence, resilience and motivation. Injuries usually cause periods away from the sports practice [16] and beyond physiological and physical attributes associated with athletes' injuries, numerous studies have linked the incidence of sports injuries to some psychological attributes e.g. stress, resilience, etc [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Injuries usually cause periods away from the sports practice [16] and beyond physiological and physical attributes associated with athletes' injuries, numerous studies have linked the incidence of sports injuries to some psychological attributes e.g. stress, resilience, etc [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given several studies have con rmed the existence of a negative relationship between resilience and anxiety like our study result [41,42], the higher level of resilience, the lower anxiety the medical staff would feel (β=-0.026, P=0.043), we could determine the resilience as a protective factor when the FLMS were confronted with the unknown and severe pandemic. The inherent implication contained in resilience explains how events are perceived and how much strength of behaviour is addressed by individuals, meanwhile, the emotional adaptation and regulation to problematic situations are highlighted through this process [43]. Furthermore, many studies have shown that higher levels of resilience not only link to improved mental health but also maintain physical health in the general population or other chronically ill populations [44,45].…”
Section: Discussionmentioning
confidence: 99%